Os direitos humanos à luz do pensamento de Hannah Arendt: perspectivas político-filosóficas - Ferreira, Ricardo Pietrowski (Universidade do Vale do Rio dos Sinos, 2015)
This dissertation aims to perform a critical analysis of how human rights’ foundation faded with the establishment of totalitarianism, and how Hannah Arendt’s thought can contribute to reflecting on (re)building such rights. It is intended to understand how the weakening of human rights ideas, diagnosed by Hannah Arendt, has developed, as well as how her reflections are essential for a construction of human rights guided by political action, freedom, plurality and equality, in a public space that guarantees human dignity. This study covers mainly the German philosopher’s thoughts; however, it is also considered some readings made by Celso Lafer, a scholar of Arent philosophy, whose works contribute to better understand human rights issues. In order to properly clarify this problem, this dissertation is organized in three parts: the first one aims at demonstrating how human rights justified and based on the declarations published in 1776 and 1789, which consider men as the source of every law and therefore as inalienable individuals, were insufficient before the totalitarian phenomena (rupture phenomenon), especially concerning stateless persons issues. The second part concerns the explanation of Arendt’s main concepts, such as: public and private space, action and discourse, human relations and responsibility, and, finally, the purpose of politics and freedom. The third part if this study focuses on Arendt’s concept of citizenship, which is defined by her as “the right to have rights”. When properly developed, citizenship enables the existence of freedom, which may be exercised through a council system. To conclude these considerations, the closing comments demonstrate how the activity of “reflective judgment”, formulated by Kant and taken into consideration by Arendt, may help with reviewing the political and philosophical thought as an assertion of freedom; therefore, it can be extremely important for administration of justice and History.
Keywords: Hannah arendt; Totalitarismo; Direito a ter direitos; Direitos humanos; Totalitarianism; Right to have rights; Human rights; ACCNPQ::Ciências Humanas::Filosofia